Electronic Word of Mouth & its Impact on Brand Associations of Algerian Consumer towards Aroma Coffee Product - Analytical Field Study – - مخلوف , سليمة (Milev Journal of Research and Studies, 2020)
The purpose of this research is to determine the effect of the electronic word of Mouth on building the Associations Brand connection of the Algerian consumer towards the Aroma coffee product. To achieve the goal of the study, the researcher gathered the necessary information through a questionnaire developed for this purpose after being subjected to a stability test. The study was conducted on a soft sample that was selected from the study population, and they are consumers of the Aroma coffee product at the national level. The sample size for which the study was conducted reached 881 individuals out of 1500 individuals. In order to reach the target results, a set of statistical methods were used, the most important of which are: ANOVA One-Way, correlation coefficients, and multiple simple regression through the forward gradient method and the hierarchical method. The study found a set of results: The study shows statistical significance no differences of in the volume of electronic word of Mouth activity on the Brand associations of the Aroma brand due to their demographic characteristics; There are statistically significant differences in the degree of Brand associations for the brand Aroma on the part of the Algerian consumer, due to its demographic characteristics; The presence of a somewhat weak moral Impact for the entirety of the electronic word of Mouth elements towards the Brand associations of the Brand study by the Algerian consumer.